Analyzing workplace arrogance and organizational effectiveness emerging research and opportunities - Tamzini, Khaled 1973-; Ayed, Tahar Lazhar (Advances in human resources management and organizational development (AHRMOD) book series, 2018)
"This book focuses on the relationship between workplace arrogance and organizational effectiveness. It addresses key themes, topics and approaches for managers, academics, students, and general readers: workplace arrogance, self-esteem, self-confidence, hubris, vanity, narcissism, job performance, job satisfaction, organizational performance, strategic scope, competence"...